Anthropogenic and Natural Drivers of Land Subsidence - Wahyudi, Rochmad; Kismartini, Kismartini; Budihardjo, Mochamad Arief; Puspita, Annisa Sila; Ammar, Marah (Universitas Diponegoro, 2026)
This review is the first attempt to integrate natural and anthropogenic drivers of coastal subsidence, the evolution of monitoring techniques, and geo-environmental impacts, with a focus on coupled human-environment systems. This review compares traditional geodetic techniques (levelling, GNSS) with other satellite and geophysical methods (InSAR, LiDAR, microgravity, and seismic survey) and assesses subsidence monitoring under different geo-environmental conditions. Empirical evidence from the northern coastline of Java, in particular Semarang, shows that subsidence has occurred at an annual rate of 2–10 + cm, which is directly linked to groundwater exploitation, alteration of land use, and coastal construction, which exacerbates tidal flooding, coastal recession, saltwater encroachment, ecosystem destruction, infrastructure deterioration, and social impacts. The findings suggest that subsidence is a unique geophysical phenomenon and not a result of anthropogenic interactions with natural systems involving water, land use, coasts, and public administration frameworks. This type of integration is essential for improved risk assessment, resilience, and sustainable development.